Características tecnológicas do vergamento das madeiras de Luehea divaricata, Carya illinoinensis e Platanus x acerifolia como subsídios para o manejo florestal. - Gatto, Darci Alberto (2006)
The present work was developed with the objective of investigating the characteristics of bending of the wood of Sycamore (Platanus x acerifolia), açoita-cavalo (Luehea divaricata), and pecan (Carya illinoinensis) coming from forests non managed for this end from the area of the Depressão Central and Encosta Superior do Nordeste of the state Rio Grande do Sul/Brasil. There were cut down five representative trees of each species and study area. There were determined the characteristics such as log as taper and idiosyncrasy. In the study there was defined the year of segregation of juvenile/adult wood by means of the radial variation of anatomical characteristics and basic density. The wood was bent in rays of 16 and 21 cm, with wood initial moisture of 14%, and after water boiling for 35 minutes. For the qualification of the defects of the bending wood, the methodology described by Vorreiter (1958) was followed. The most probable year of segregation is the defined by the radial variation of fiber length that was determined, respectively as, 21, 16 and 14 years for açoita-cavalo, pecan and sycamore. With relationship to the quality of the wood bending, the juvenile wood was surprisingly better than the adult wood for the rays and tested species. In this resard, there are not great needs of a forest handling that decreases the amount of juvenile wood. Nevertheless, trunk breakdown should be made respecting the direction of the fibers; thus, avoiding the main defect of the wood bending (splintering by tension). The best results of the bending wood were observed for the wood of pecan. Possibly, the ring porous wood, characteristic of the species, contributed in the result. Meanwhile, açoita-cavalo and sycamore, wood with diffuse porosity and of high parenchyma proportion, presented a great amount of defective pieces.